2022
DOI: 10.1155/2022/9653244
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells: From an Insight into the Basics to Recent Advances and Therapeutic Targeting

Abstract: Cancer is characterized by an abnormal growth of the cells in an uncontrolled manner. These cells have the potential to invade and can eventually turn into malignancy, leading to highly fatal forms of tumor. Small subpopulations of cancer cells that are long-lived with the potential of excessive self-renewal and tumor formation are called cancer stem cells (CSCs) or cancer-initiating cells or tumor stem cells. CSCs can be found in tissues, such as breast, brain, lung, liver, ovary, and testis; however, their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 170 publications
0
18
0
Order By: Relevance
“…However, the relevance of metformin to counteract drug resistant cancer development has not been well studied. In a recent review, the ability of metformin to inhibit the activity of cancer stem cells was considered [ 20 ]. It has been found that metformin can increase the sensitivity of cancer stem cells to chemotherapy through a variety of methods, including improving vascular normalization and suppressing tumor angiogenesis in metastatic breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relevance of metformin to counteract drug resistant cancer development has not been well studied. In a recent review, the ability of metformin to inhibit the activity of cancer stem cells was considered [ 20 ]. It has been found that metformin can increase the sensitivity of cancer stem cells to chemotherapy through a variety of methods, including improving vascular normalization and suppressing tumor angiogenesis in metastatic breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are self-renewal cells, which can promote the occurrence and metastasis of tumors and enhance the drug resistance of tumor treatment [4]. Transcriptomebased studies in multiple tumors have revealed a significant link between tumor stemness and patient prognosis and tumor immune microenvironment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the tumor stemness has attracted much attention. The main characteristics of tumor stemness are the strong self-renewal ability and increased tumor heterogeneity [ 3 4 ]. Many studies have shown that tumor stemness plays an important role in tumor metastasis, differentiation, and drug resistance [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and understanding CSCs will increase cancer diagnosis methods and enhance early patient stratification, leading to new and more efficient therapies specifically targeting this fraction of tumor cells and the improvement of the overall outcome of CRC patients [ 33 , 34 ]. As a consequence, we combined clinical settings with fundamental research, in order to assess genetic methods of identifying and characterizing CSCs.…”
Section: Discussionmentioning
confidence: 99%